A Textbook Evaluation On English Textbook Entitled “Grow With English” Used By Students Of MI Nurul Huda Bengkulu City - Reko Serasi; Levina Fatimah; M Arif Rahman Hakim; Dian Anggraini (AL LUGHAH, 2021)
Based on the perception of the teacher and students in Madrasah Ibtidaiyyah (MI) Nurul Huda Bengkulu City when the researchers conducted an observation, the textbook is suitable for use in the teaching and learning process. Based on those perceptions, this study was intended to evaluate the quality on English textbooks Grow with English published by Erlangga Publisher used by students grade V and IV of MI Nurul Huda Bengkulu city with how much it meets the requirement of good EFL textbook considered four criteria, namely: (1) Subjects  and Contents; (2) Skills and Sub-skills; (3) Layout and Physical Make-up; and (4) Practical Consideration viewed by teacher and see students perception about these textbooks. This study used a quantitative research approach. Total population of this study were 114 students and 1 english teacher. Samples of this research were 25% of the population or 29 students which divided into 2 grades. 15 students from 5th grade and 14 students taken from 4th grade. In collecting data, researchers used checklist as the instrument which adapted from Demir and Ertas. Both textbooks was qualified based on the score ranges which divided into very bad (0-20), bad (21-40), fairly good (41-60), good (61-80), very good (81-100). The result of this study was first, Grow with English for grade five was categorized as good toward the four criteria of good EFL textbook requirements. It reached 79,78% of total score while 80,48% by students’ perception and 79,08% viewed by teachers’s perspective. Second, Grow with English for grade four was categorized  as  good  because  the  total  score  toward  the  four  criteria  is 77,77%. The total score was gained from 80,9% based on students’ perception and 74,65% viewed by teacher’s perspective. So based on the result of this study, it can concluded that both of textbooks met the criteria in fulfilling the requirements of good EFL textbook criteria covering the availability of materials based on Subjects and Contents, Skills and Sub-skills, Layout and Physical Make-up, and the Practical.